2010
DOI: 10.15261/serdj.17.151
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction and Stripping of Gold(III) from Hydrochloric Acid Solution Using Vacuum Pump Oil

Abstract: Vacuum pump oil (VPO) in toluene was employed as a solvent extraction reagent for Au(III) from HCl. The effects of shaking time and concentration of HCl on the extraction of Au(III) were investigated. It was found that the selectivity of VPO for Au(III) was superior even to dibutylcarbitol (DBC) which is currently employed as a commercial extactant for gold. The extraction of Au(III) with VPO is nearly quantitative over the whole HCl concentration range, while the extraction of other metal ions is nearly negli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Xiong et al reported on the extraction isotherm for Au(III) in 3 M HCl using DBC [10]. The maximum ).…”
Section: Selectivity Of Metal Extraction Using Cpme In Hydrochloric Amentioning
confidence: 99%
See 2 more Smart Citations
“…Xiong et al reported on the extraction isotherm for Au(III) in 3 M HCl using DBC [10]. The maximum ).…”
Section: Selectivity Of Metal Extraction Using Cpme In Hydrochloric Amentioning
confidence: 99%
“…In the extraction system using DBC, extracted gold is reductively stripped as metallic gold using an aqueous oxalic acid solution [10,14]. Rreductive stripping using oxalic acid was not investigated for CPME in this study.…”
Section: Back Extraction Of Au(iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Under acidic conditions, thiourea is easily protonated by hydrogen ion, and the stability of thiourea protonated at the S atom is stronger than that at the N atom 33 . Therefore, adding dilute hydrochloric acid can increase stripping efficiency of thiourea 34 . Some more stripping experiments were done by employing the mixture of thiourea with either HCl and H 2 SO 4 solution.…”
Section: Resultsmentioning
confidence: 99%
“…SO 4 . Such effective stripping of Au(III) with thiourea is due to the high affinity of thiourea for gold ions: it is known to form a stable cationic complex[22].…”
mentioning
confidence: 99%